Assessing the Effectiveness of Teachers’ Mental Health Literacy Training in Cambodia: A Randomized Controlled Trial - Phoeun, Bunna; Nguyen, Amanda J; Dang, Minh Hoang; Tran, Nam Thanh; Weiss, Bahr (VNU Journal of Science: Education Research; Vol 35 No 3DO - 10.25073/2588-1159/vnuer.4279, 2019)
School-based mental health literacy (MHL) programs are used to reduce stigma and promote help-seeking among students and teachers. This study aimed to adapt and evaluate a teacher-delivered MHL program in Cambodia, where the impact of MHL programs has not previously been evaluated. 67 teachers and 275 students from a high school in Phnom Penh voluntarily completed the study. School staff were randomly assigned, and classrooms purposively assigned, to either a 2-day MHL training program or a control condition. Four teachers in the intervention condition were also pragmatically selected to deliver a 6-week classroom MHL curriculum to students; these teachers receive an extra day of implementation training. Teacher and student MHL were assessed before and after the intervention. Results showed significant improvements in all indicators of teacher and student knowledge and attitudes about mental illness; largest improvements were in teachers’ perceptions of dangerousness and willingness to interact. This pilot RCT supports the potential benefits of school-based MHL training in Cambodia, where there is substantial mental health stigma and discrimination. However, small to moderate effect sizes, particularly for students outcomes, suggest a need for further refinement and testing of the curriculum to optimize impact, including further consideration of implementation strategies and supports.